Can High Altitude Influence Cytokines and Sleep?. (9th April 2013) - de Aquino Lemos, Valdir; dos Santos, Ronaldo Vagner Thomatieli; Lira, Fabio Santos; Rodrigues, Bruno; Tufik, Sergio; de Mello, Marco Tulio
Abstract : The number of persons who relocate to regions of high altitude for work, pleasure, sport, or residence increases every year. It is known that the reduced supply of oxygen (O2 ) induced by acute or chronic increases in altitude stimulates the body to adapt to new metabolic challenges imposed by hypoxia. Sleep can suffer partial fragmentation because of the exposure to high altitudes, and these changes have been described as one of the responsible factors for the many consequences at high altitudes. We conducted a review of the literature during the period from 1987 to 2012. This work explored the relationships among inflammation, hypoxia and sleep in the period of adaptation and examined a novel mechanism that might explain the harmful effects of altitude on sleep, involving increased Interleukin-1 beta (IL-1 β ), Interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF- α ) production from several tissues and cells, such as leukocytes and cells from skeletal muscle and brain.